Hurricane Katrina, 2005 - Tarshis, Lauren; Dawson, Scott (New York : Scholastic, 2011)
Barry becomes separated from his family during Hurricane Katrina. How can he survive away from his family? Tells the story of how this storm affected one family in New Orleans.
Keywords: Hurricane Katrina, 2005 -- Juvenile fiction; Hurricanes -- Juvenile fiction; Disaster victims -- United States -- Juvenile fiction; Survival -- Juvenile fiction; Adventure stories; Historical fiction